Myxobolus leafa sp. nov. (Myxozoa: Bivalbulida) from the gill filament of Labeo bata (Hamilton) from Manipur, India - Thounaojam, Hemananda; Mohilal, Naorem; Bandyopadhyay, Probir K; Mitra, Amlan Kumar; Gürelli, Gözde (Galenos Yayinevi, 2013)
The aim of this study was to investigate the gill filaments of Labeo bata in India parasitologically and to describe the new Myxozoa parasite species, Myxobolus leafa sp. nov., which was determined.Fish were collected alive from fish farms from Manipur (India). Sporogonic plasmodia were removed with sterile forceps and observed under phase contrast microscope. For permanent preparations, air dried smears were stained with Giemsa after fixation in acetone free absolute methanol.Mature spores of the new species appear as leaf-like structures in valvular or frontal view, tapering at both ends. The anterior end of the spore is broader than the posterior end. Spores measure 15.3-11.8 μm (16.91 ± 1.16) in length and 13.6-15.3 μm (14.15 ± 0.67) in breadth.The new gill parasite species, Myxobolus leafa sp. nov., was described from fish in India. The prevalence of the parasite was 3.3% and two stages (cyst and spore) of the parasite existed in its life cycle.
Keywords: Gills; Spores; Fish Diseases; Life Cycle Stages; Microscopy; Myxobolus; Parasitic Diseases, Animal; Cyprinidae; Animals; India